Random Latin Square Based Fast Frequency Hopping Scheme for Physical Layer Security in OFDM Systems - Hyeon, Seokjun; Baek, Hoki; Lim, Jaesung (Journal of Korean Institute of Communications and Information Sciences, 2021)
Recently, there is a need to introduce a tactical data link using a high-efficiency OFDM (Orthogonal Frequency Division Multiplexing) waveform capable of transmitting high-capacity command and reconnaissance tactical information as well as remote operation of new military platforms such as intelligent weapon systems such as UAVs. In the conventional tactical data link system such as Link-16, FHSS (Frequency Hopping Spread Spectrum) technology has been applied to ensure a high level of low detectability. However, since the OFDM system uses a wide frequency bandwidth, there are many limitations to applying the FHSS technique as it is. Therefore, in this paper, we propose a fast frequency hopping technique (SecFFH/OFDM) that applies Latin Square to FFH (Fast Frequency Hopping) OFDM as a solution to this problem. This is a method in which one symbol randomly hops all subcarriers of the system within the OFDM symbol time, and provides secret communication in which only the transmitting end and the receiving end knowing the hopping pattern can communicate normally. In order to verify this, it was performed in MATLAB, and it was verified that the proposed technique can be used as a physical layer encryption technique requiring low detectability.
Keywords: Frequency Hopping; OFDM(Orthogonal Frequency Division Multiplexing); Physical Layer Security; Secure Communication; Tactical Datalink